Frindle - Clements, Andrew 1949-; Selznick, Brian (New York Scholastic Inc., 1996)
When he decides to turn his fifth grade teacher's love of the dictionary around on her, clever Nick Allen invents a new word and begins a chain of events that quickly moves beyond his control.
"Winner of the Christopher award."
Keywords: Teacher-student relationships -- Fiction; Words, New -- Fiction; Schools -- Fiction